The Frizzled family: receptors for multiple signal transduction pathways - Huang, Hui-Chuan (BioMed Central, 2004)
Frizzled genes encode integral membrane proteins that function in multiple signal transduction pathways. They have been identified in diverse animals, from sponges to humans. The family is defined by conserved structural features, including seven hydrophobic domains and a cysteine-rich ligand-binding domain. Frizzled proteins are receptors for secreted Wnt proteins, as well as other ligands, and also play a critical role in the regulation of cell polarity. Frizzled genes are essential for embryonic development, tissue and cell polarity, formation of neural synapses, and the regulation of proliferation, and many other processes in developing and adult organisms; mutations in human frizzled-4 have been linked to familial exudative vitreoretinopathy. It is not yet clear how Frizzleds couple to downstream effectors, and this is a focus of intense study.